IMPACT OF COMORBIDITY AND PROGNOSIS ON HIP FRACTURE AND MORTALITY INCIDENCE AMONG WOMEN IN LATE LIFE. (11th November 2018) - Ensrud, K; Kats, A; Boyd, C; Diem, S; Schousboe, J; Taylor, B; Bauer, D; Langsetmo, L
Abstract: Concerns about comorbidities and limited life expectancy increase the complexity of managing osteoporosis in late life. To determine effects of comorbidity burden and prognostic information on cumulative incidence of hip fracture among osteoporotic women in late life with and without accounting for competing risk of mortality, we studied 1115 osteoporotic community-dwelling women (mean age 84.6 years, SD 3.6) with assessment of 14 comorbid conditions (self-report) and prognosis (validated mortality prediction index incorporating demographics, functional status and medical diagnoses). Women were contacted every 4 months to ascertain vital status and hip fracture. During the 5-year follow-up period, 126 (11.3%) experienced a hip fracture and 204 (18.3%) died before experiencing this event. Hip fracture and mortality incidence were both higher with increasing comorbidities and worsening prognosis. Among women with the highest comorbidity burden (≥3 conditions), hip fracture probability was 18.7% at 5 years using the Kaplan-Meier method versus 16.6% using a competing risk approach. Among women with the worst prognosis, hip fracture probability was 23.0% at 5 years using the Kaplan-Meier method versus 19.5% using a competing risk approach. In summary, taking into account the higher competing risk of mortality among community-dwelling osteoporotic women with greater comorbidity burden or poorer prognosis modestly attenuated their 5-year hip fracture probability. These results suggest that osteoporotic women in late life with high comorbidity burden may still be candidates for drug treatment to prevent hip fracture, even considering their competing risk of mortality. Data regarding efficacy and safety of drug treatment in this population is needed.